Elimination of Pharmaceutical Pollutants by Solar Photoelectro-Fenton Process in a Pilot Plant - Salazar-Gonzalez, R; Toledo-Neira, C; Toledo-Neira, C (Springer Science and Business Media Deutschland GmbH, 2021)
In this study, the simultaneous degradation of antibiotics (ampicillin, sulfamethazine, and tetracycline; and non-steroidal anti-inflammatories (diclofenac and salicylic acid)) including the total organic carbon abatement by solar photoelectro-Fenton process was assessed. Eight liters of solution containing the mixture of the five pharmaceuticals in 1 mmol L−1 Fe2+, 0.05 mol L−1 Na2SO4 at pH 3 and 35 °C were electrolyzed applying different current densities (j = 10, 25, and 50 mA cm−2) in a solar-electrochemical pilot plant. The pilot plant was equipped with an electrochemical filter press cell with a dimensionally stable anode (DSA type) and an air-diffusion cathode coupled to a solar photoreactor exposed directly to sunlight radiation. All pharmaceuticals were degraded during the first 10 min. A TOC removal efficiency of 99.2% after 100 min of treatment with an energy consumption of 534.23 kW h (kgTOC)−1 and 7.15 kW h m−3 was achieved. The pharmaceutical concentration decay followed a pseudo-first-order kinetics. The specific energy per unit of mass of ampicillin, diclofenac, salicylic acid, sulfamethazine, and tetracycline was obtained at 11.73, 19.56, 35.2, 11.73, and 39.32 kW h (kgPD)−1 for ampicillin, diclofenac, salicylic acid, sulfamethazine, and tetracycline, respectively. With our results, we demonstrated that SPEF is an emerging technology for the treatment of this type of pollutants in short time. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.